Simulation of cardiac emergencies with real patients. (5th June 2015) - Williams, Howell; Yang, Lisa; Gale, Jessica; Paranehewa, Sakitha; Joshi, Abhishek; Westwood, Mark; Weerackody, Roshan
Summary Background Simulation training with manikin simulators for medical emergencies is increasingly used in medical training. The assessment of a manikin, in particular history and examination, is very different to that of a real patient. We sought to combine aspects of traditional simulation training with the assessment of real hospital in‐patients. Study design In‐patients who had recently experienced a cardiac emergency were asked to recall their symptoms as if they were still present. Medical students assessed these patients in the role of foundation year–1 (FY1) doctors, supervised by core medical trainee (CMT) doctors, and were encouraged to formulate a differential diagnosis and initial management plan. The students filled in a questionnaire prior to, immediately after and 1 week after each simulation session. This included a self‐assessment of confidence in managing cardiac emergencies, as well as knowledge‐based questions on aspects of assessment and management of cardiac emergencies. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> We sought to combine aspects of traditional simulation training with the assessment of real hospital in‐patients </boxed-text> Results Confidence in managing cardiac emergencies was initially low, but significantly increased after one simulation training session (p < 0.001). This increase was sustained on re‐assessment 1 week after the training session (p < 0.001). In addition to the increase in confidence, a significant and sustained increase in knowledge score was also observed (p < 0.001). Conclusion Simulation training with real patients led to an immediate and sustained increase in self‐assessed confidence. There was also an increase in medical knowledge of the assessment and management of cardiac emergencies. This simulation technique is inexpensive, easily reproducible and can be used to complement learning from traditional simulation training with manikins.